“Nós somos os heróis brasileiros”: o trabalho de caminhoneiros de rota longa que abastecem a Cooperativa dos Hortigranjeiros do Maranhão - CASTRO, Luciana Campos (2021)
In Brazil, the work of truck drivers has great relevance and impact on the economy, since more than 60% of the total volume of cargo is transported by highways, through truck drivers. In this sense, the interruption of this work generates numerous economic and social losses. However, studies show that the conditions and long working hours to which they are subjected on a daily basis can have consequences for the health of these workers. Therefore, this research sought to analyze the work dynamics of long-haul truck drivers who supply the Cooperativa dos Hortigranjeiros do Maranhão (CEASA-MA), in the city of São Luís/MA. To this end, it adopted a theoretical-methodological proposal of a qualitative nature, supported by the conceptual approach of Psychodynamics of Work in conjunction with Historical-Dialectical Materialism, prioritizing the following categories: pleasure, suffering, coping strategies, recognition and meanings of work. The empirical research had a questionnaire to map the sample and a semi structured interview as data collection instruments. 18 truck drivers answered the questionnaire and 08 long-haul truck drivers participated in the interview, five of them self-employed and three employees, all with more than one year of experience in the profession. Truck drivers are part of a very heterogeneous class of workers, however it is possible to glimpse some approximations between the activity of the self-employed and employees. It was found that in the face of suffering, drivers make use of coping strategies such as denial and adaptation, also resorting to the use of substances such as rivet, alcohol and tobacco. That is, looking for individual ways to withstand the excesses of work and not get sick. Despite the difficulties, truck drivers manage to experience pleasurable experiences and, even in the face of the lack of social recognition, for most drivers, for the work done, all of them are still able to experience an activity that offers some meanings.